Vascular cause amputations. Level selection - López Chapuis, Daniel; Esperón, Alejandro; Vallverdú, Martín; Gómez Fossati, Carlos (Cirugía del Uruguay, 1996)
Amputation is a frequent and sometimes unavoidable consequence on the evolution of the ischemic vascular disease of /ower limbs. The right selection of amputation levels is fundamental to achieve a fast cicatrization, avoiding complications and offer the patient the best possibilities of rehabilitation by means of a prosthesis The authors reviews c!inica/ and paraclinica/ factors, useful in the election of appropriate amputation leve! to fu/fil! this objectives